The association between social characteristics, alcoholic beverage preferences, and binge drinking in a Serbian adult population. Issue 1 (February 2019) - Pakovic, Ljubica; Todorovic, Jovana; Santric-Milicevic, Milena; Bukumiric, Dragica; Terzic-Supic, Zorica
Aim: To determine the association of sociodemographic characteristics and type of alcoholic beverage consumed during binge drinking in Serbia. Method: We conducted a secondary analysis of data from the 2014 national survey on Serbian lifestyles focusing on substance abuse and gambling. The sample consisted of 5385 individuals. The respondents were divided into non-binge drinkers and binge drinkers, according to the quantity of alcohol consumed during one occasion. Binge drinkers reported consuming more than 60 g of pure alcohol (7.5 units of alcohol) during one occasion at least once during the previous year. Results: The prevalence of binge drinking in the past year among 2676 female and 2709 male participants aged 18–64 years was 28.4%. The multivariate logistic regression model showed that binge drinkers were more likely to be male (95% CI 3.58–4.94), single (95% CI 1.01–1.53), to be former (95% CI 1.06–1.62) or current smokers (95% CI 1.57–2.19), and to consume more than one type of alcoholic beverage (95% CI 2.04–3.44). There was a negative association of binge drinking with age (95% CI 0.98–0.99), living outside Northern Serbia-Vojvodina region, and drinking only spirits (95% CI 0.39–0.93). Conclusion: Focusing on the positive association of sociodemographic factors and binge drinking could help policy makers create public health interventions against alcohol misuse. These interventions should be directed to males, smokers, and those who consume more than one type of alcoholic beverage.